Marketing Resilience Capability for Sustainable Customer Relationships - Mufti Fahrizal Harahap (Involvement International Journal of Business, 2026)
Increasing environmental uncertainty, rapidly changing customer expectations, technological disruption, and intensified competition have challenged organizations to sustain long-term customer relationships using conventional marketing approaches. This study aims to conceptualize Marketing Resilience Capability (MRC) as a higher-order organizational capability that enables firms to anticipate, adapt to, and recover from market disruptions while preserving sustainable customer relationships. A qualitative multiple-case study design was employed involving organizations operating in the retail, service, and digital business sectors recognized for maintaining stable customer relationships during periods of market uncertainty. Data were collected through semi-structured interviews with senior marketing managers and customer relationship executives, complemented by organizational documents, customer communication materials, and field observations. The data were analyzed using thematic analysis supported by the constant comparative method. The findings identify four interrelated dimensions of Marketing Resilience Capability namely adaptive market sensing, relational responsiveness, customer value reconfiguration, and relationship continuity management. Adaptive market sensing enables organizations to detect emerging market changes proactively; relational responsiveness strengthens customer trust through transparent and empathetic communication; customer value reconfiguration continuously aligns organizational offerings with evolving customer expectations; and relationship continuity management institutionalizes sustained customer engagement beyond transactional exchanges. Collectively, these capabilities enable organizations to maintain customer confidence, loyalty, and relationship continuity despite dynamic market conditions. The study further demonstrates that sustainable customer relationships are achieved not solely through superior products or operational excellence but through continuous organizational adaptation and relational capability development.